Starting Torque Reduction of Direct Torque Control Based Synchronous Motor Using Simulated Annealing - Amir Hamzah Pohan; Lady Diana Warpindyastuti (Jurnal Teknik, 2020)
The motion control of a container port on an industrial conveyor involves non-linear movement by varying the speed  of the conveyor. The stability control of the conveyor system is in the starting current or starting torque of the synchronous motor. The starting performance of the motor requires rapid dynamics and precise regulation, hence the need of a direct control is becoming an urgent demand. A non-linear movement for the starting current of the motor can be effectively controlled through simulation. A synchronous motor is usually specified when constant speed and the power factor correction is required. However, subject to many loads, the starting current and starting torque heat up the fuse of the armature rotor and stator. Full state feedback control through simulation has been shown as not being able to stabilize a conveyor movement. Therefore, the need for direct control is important to stabilize the system. The starting current at a synchronous motor should be able to perform better, even for cases where the controlling parameter model was uncertain or changing over time. A reference of any controller model will be selected to stabilize the non-linear motion of the motor. Then the simulation studies will be performed to observe the performance with any controller on starting current of motor. A one objective simulated annealing will be used to optimize the system in decreasing a starting current synchronous motor. Keywords:  A synchronous motor, Non linear, one objective  simulated  annealing,  starting torque , parameter model